PELATIHAN DAN PENYUSUNAN RENCANA STRATEGIS (RENSTRA) SENTRUM PENGEMBANGAN PERTANIAN TERPADU (SP2T) BOLU-TORAJA UTARA - Papalangi, Nataniel; Amos, Viktor (Jurnal Bakti Masyarakat Indonesia, 2023)
Sentrum Pengembangan Pertanian Terpadu (SP2T) that oversees a considerable land area with an integrated agricultural development program is expected to thrive ef ectively. For this purpose, a Strategic Plan needs to be formulated. In the development of the Center for Integrated Agricultural Development (SP2T) for Socio-Economic Empowerment of the Archdiocese of Makassar (PSE KAMS), it is highly desirable that SP2T evolves into a self-sustaining learning institution in terms of financing, thereby reducing dependency on future proposal funding. The confidence in the outcomes of integrated agricultural processing should be substantiated, as consistently emphasized during the conducted training sessions. SP2T should not merely serve as a learning platform but also be capable of sustaining itself. Meanwhile, based on business analysis, this could feasibly be achieved through agricultural and livestock enterprises. The Integrated Agricultural Development Center of Bolu (SP2T Bolu) is located in Bolu, North Toraja Regency. This organization operates as a non-profit organization (NPO) with the aim of becoming a hub for developing local crop agriculture and managing livestock. Crop agriculture includes crops like cof ee, fruit-bearing plants, and vegetables, while livestock includes broiler chickens, meat chickens, pigs, and goats. In the context of agricultural development, ef orts are made to render the land productive, transforming it into a laboratory and a model for agriculture by managing funds from KAMS and sponsors. In the context of livestock, ef orts are directed toward livestock development. ABSTRAK: Pengelolaan Sentrum Pengembangan Pertanian Terpadu (SP2T) yang mengelola lahan yang cukup luas dengan program pengembangan pertanian terpadu diharapkan dapat berkembang dengan baik. Untuk Maksud tersebut perlu disusun rencana Strategis. Dalam pengembangan Sentrum Pengembangan Pertanian Terpadu (SP2T) Pemberdayaan Sosial Ekonomi Keuskupan Agung Makassar (PSE KAMS), sangat diharapkan SP2T bergerak menjadi tempat pembelajaran yang mandiri dalam pembiayaan sehingga tidak tergantung pada dana proposal di kemudian hari. Keyakinan akan hasil dari pengolahan pertanian terpadu seharusnya bisa dibuktikan sebagaimana selalu diajarkan dalam pelatihan – pelatihan yang dilakukan sehingga SP2T tidak menjadi lembaga yang semata jadi media pembelajaran tapi tidak mampu menghidupi dirinya sendiri. Sementara dari analisa usaha hal ini sangat mungkin dilakukan melalui usaha pertanian dan peternakan. Sentrum Pengembangan Petanian Terpadu Bolu (SP2T Bolu) terletak di Bolu, Kabupaten Toraja Utara. Lembaga ini merupakan non profit organization (NFO) yang berupaya menjadi pusat pengembangan pertanian tanaman rakyat dan mengelola peternakan. Pertanian tanaman seperti kopi, tanaman buah dan sayuran sedangkan untuk peternakan seperti ayam potong, ayam pedaging, babi dan kambing. Dalam konteks pengembangan pertanian berupaya menjadikan lahan menjadi produktif dengn menjadi salah satu laboratorium dan percontohan pertanian dengan mengelola dana dari pihak KAMS dan sponsor. Dalam konteks peternakan berupaya melakukan pengembangan peternakan.